Non-equilibrium many-body states in carbon nanotube quantum dots : doctoral thesis accepted by Osaka University, Osaka, Japan /: doctoral thesis accepted by Osaka University, Osaka, Japan. (2019) - Hata, Tokuro
No abstract available